SEBARAN DAN KORELASI MINERAL KRITIS PADA ENDAPAN SKARN Pb-Zn DI DESA CIHAUR, KABUPATEN SUKABUMI, JAWA BARAT - Rizal, Khairu; Nurkhamim; Idrus, Arifudin (Balai Besar Pengujian Mineral dan Batubara tekMIRA, 2025)
This research investigates ore samples from Cihaur Village, Sukabumi District, West Java, which exhibit significant skarn alteration in limestone, is examined for its petrographic and mineragraphic features. Secondary minerals identified include pyroxene, garnet, calcite, and opaque minerals, while the primary ore minerals are chalcopyrite (CuFeS2), galena (PbS), and sphalerite (ZnS). Five samples were analyzed geochemical analysis using the ICP-MS method to assess the concentration of important elements including Pb, Zn, Cu, Ag, Sb, Bi, Cd, Mg, Al, Ca, Fe, and As. Element distribution patterns were examined using spider diagrams, providing insight into environmental gradients influencing mineral exploration. The study revealed a high positive correlation between Pb and Zn, suggesting co-deposition in sulfide mineralization. Pb also correlates strongly with Ag and Sb. This study confirms the considerable economic potential of the Sukabumi skarn deposits for Pb, Zn, Cu, and precious metals such as Ag. Exploration value is increased when essential minerals like Sb and Cd are present. Variations in geochemical conditions indicate the influence of magmatic intrusions and hydrothermal activity on element distribution. These results provide a solid foundation for further exploration to delineate mineralization zones in the region